Pengaruh Ekstrak Daun Paku Resam (Gleichenia linearis Burm.) Terhadap Pertumbuhan Gulma Putri Malu (Mimosa pudica L) - Mukarlina, Emi Kurniawati, Elvi Rusmiyanto Pancaning Wardoyo, (Universitas Tanjungpura, 2018)
Gleichenia linearis is a wide-leaved weed that contains allelochemical compounds of flavonoids, triterpenoids, saponins, tannins, alkaloids and steroids that can inhibit the growth of other plants, so it can be used as bioherbicide. This research aims to determine the concentration of G. linearis leaf extract capable of inhibiting germination and growth of Mimosa pudica weed. This research was conducted at the Laboratory and Screen House of the Department of Biology Faculty of Mathematics and Natural Sciences, at the Chemistry and Soil Fertility Laboratory and at the Wood Technology Laboratory of the Faculty of Forestry, Tanjungpura University Pontianak from February to April 2016. This research used a Completely Randomized Design (RAL) with 5 replications consisting of control, 0.1; 0.3; 0.5 and 0.7 g/ml. The treatment of germination and growth started from control, 0.1; 0.3; 0.5 and 0.7 g/ml. The results showed that the concentration that could inhibit M. pudica weed germination was the 0.5 g/ml concentration and its growth was the 0.5 g/ml concentration.